Drugs in sport - Mottram, D. R.; Chester, Neil (Routledge, Taylor & Francis Group, 2018)
Drugs in Sport is the most comprehensive and accurate text on the emotive, complex and critical subject of doping and illegal performance enhancement in sport. Thoroughly updated in light of the latest World Anti-Doping Code and taking into account the latest regulations, methods and landmark cases, this seventh edition explores the science behind drug-use in sport, as well as its ethical, social, political and administrative context.